11. THE RESULT OF TREATMENT OF SUPRAVENTRICULAR TACHYCARDIA IN THE EMERGENCY DEPARTMENT, VIETNAM NATIONAL CHILDREN'S HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Objective: To evaluate the results of emergency treatment of supraventricular tachycardia inchildren according to the APLS 2021 protocol at the Emergency Department - National Children’sHospital. Subjects and research methods: Children who were diagnosed with supraventriculartachyarrhythmias when admitted to the Emergency - Anti-toxicity Department of the NationalChildren’s Hospital. Results: Children over one year old accounted for the majority (76%). Thereare 46 cases of successful cessation, accounting for 92%. Treating supraventricular tachycardia ismainly used with drugs (accounting for 90), in which adenosine is primarily used (96%). There were76.6% cases of successful cessation with adenosine and the highest rate of successful termination ofthe second dose, accounting for 57.7%. The rate of successful cessation in the group of children underone year old and over one year old did not have a statistically significant difference (p>0.05). Therate of acute heart failure decreased compared to before cessation with a difference with statisticalsignificance p < 0.05. Conclusion: Adenosine is an effective, safe, first-choice drug in managingsupraventricular tachycardia in children.
Keywords: Treatment results, supraventricular tachycardia, National Children’s Hospital.